Three-Dimensional Virtual Reality Simulation to Safe Planning Neurosurgical Procedure in Brain Aneurysms, Latin American Single-Center Experience: Advantages and Limitations - Antonio M. Zárate-Méndez; José M. Ramos-Delgado; Juan C. Lujan-Guerra; Carlos D. Rio-Olivares; Luis E. Moreira-Ponce; José L. Aceves-Chimal (Indian Journal of Neurosurgery)
Background The neurosurgical approach to clipping cerebral aneurysms has been a complex challenge for all neurosurgeon experts in cerebrovascular surgery. The three-dimensional computed tomography angiography (3D-CTA) allows identifying bone and vascular structures close to an aneurysm to simulate in virtual 3D images, the appropriate and safest approach to cerebral aneurysm clipping. Objectives This study aims to share our experience using 3D simulation as a support to the safe planning for cerebrovascular disease surgery. Materials and Methods We reviewed the surgical outcomes from a cerebrovascular neurosurgeon using the 3D-CTA images in 360-degree reconstruction in the planning of the preoperative surgical procedure for the treatment of brain aneurysm. In all patients, the virtual surgical approach was replicated in real-time surgery. Results We analyzed 34 patients around 51 ± 8 years of age. Of these, 76.5% (n = 26) and 23.5% (n = 8) were males and females, respectively. Saccular aneurysms were the most frequent (85%), the Arteries affected by aneurysms were middle cerebral artery (n = 6), basilar tip (n = 6), vertebral artery in V3 and V4 (n = 6), and posterior cerebral artery (n = 5). The virtual surgical pterional approach was the most frequently used (50%), followed by fronto-orbito-zigomático (29%) and far lateral (15%) approaches. There were no intraoperative complications in any patient. Conclusion Preoperative 3D virtual reality simulation is a great support tool to perform a safe surgical procedure in real-time for the treatment of simple and complex brain aneurysms.